Cyclohexanone Oxidation over H3PMo12O40 Heteropolyacid via Two Activation Modes Microwave Irradiation and Conventional Method - Yasmina Idrissou; Sihem Mouanni; Catherine Marchal-Roch; Cherifa Rabia; Dahbia Amitouche; Tassadit Mazari (Bulletin of Chemical Reaction Engineering & Catalysis, 2019)
The adipic acid (AA), important precursor for Nylon production, was synthesized from cyclohexanoneoxidation by two ways, microwaves irradiation and  conventional method (under reflux) using H3PMo12O40 heteropolyacid as catalyst in the presence of hydrogen peroxide. In the order to increase the AA yield, several parameters as cyclohexanone/catalyst ratio, H2O2 concentration, solvent nature (H2O, CH3CO2H, and CH3OH, CHCl3 and CH3CN) and cyclohexanol addition to cyclohexanone were examined.  For both activation modes, the highest AA yields are of 26-28%. Whereas, with microwaves irradiation, the time gain is much more attractive 30 min compared to 20 h.